Determination of the Positions of the Nutrient Foraminae in the Human Adult Lower Limb Long Bones (Medical Forum Monthly, 2024)
Objective: To determine the positions of the nutrient foraminae (NF) in the human adult lower limb long bones.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Forensic Medicine and Anatomy Departments of Nowshera Medical College, Nowshera and Ayub Medical Colleges, Abbottabad, K.P.K. from March to July 2018.Materials and Methods: Thisstudy was done on 90long bones of the lower limb. After inclusion and exclusion criteria, total number, position,and direction of all of the foraminae were observed macroscopically. The foraminal index was calculated by Hughes H formulae and divided into three types.Results: In the case of femora, (79.61%) of NF were located along the middle third of the diaphysis. While rest was in Proximal 3rd, the distal 3rd had no foraminae. In cases of tibiae, 83.3% were located on the Proximal 3rd. The rest of NF were located in the middle 3rd. The distal3rd had no foraminae. In cases of fibulae, most of the NFwere located on the middle 3rd (97.2%). This distal 3rd of the bones had rest of the foraminae (2.8%).Conclusion: Our study confirmed the previous reports regarding the number and position of the NF in the human long bones of the lower limbs. The variation in NF is also very important in forensic radiology, anthropometry, and differentiation of human and non-human bones.